Anticipating the Impact of the Patient Protection and Affordable Care Act for Patients with Urological Cancer - Ellimoottil, Chandy (2014)
The Affordable Care Act seeks to overhaul the US healthcare system by providing insurance for more Americans, improving the quality of healthcare delivery, and reducing healthcare expenditures. While the law’s intent is clear, its implementation and effect on patient care remains largely undefined. Herein, we discuss major components of the ACA, including the proposed insurance expansion, payment and delivery system reforms (e.g. bundled payments and Accountable Care Organizations) and other reforms relevant to the field of urologic oncology. We also discuss how these proposed reforms may impact patients with urological cancers.